Percepção das meninas do ensino médio sobre o curso de computação no Distrito Federal do Brasil - Holanda, Maristela (2017)
Abstract—In the last years, the field computer science has been of little interest for girls attending the undergraduate courses in Brazil. In the Computer Science Department at the University of Brasília, in the country’s capital, female students compose less than 10% of the student body. To try to understand the girls’ lack of interest in computer related courses, this article analyses data from a poll done with high school girls in Brazil’s Distrito Federal from 2011 to 2014.